Žiemgalių antkaklės XII-XIII amžiuje - Vasiliauskas, Ernestas (Archaeologia Lituana, 2005)
In the 12-13th centuries the custom of wearing neck-ring was disappearing. This period sees only the last evolutionary phase of neck-rings ending with hook and loop. The 12-13th centuries saw the neck-rings of new forms to become widespread - spiral neck-ring with flattened terminals, wire wound band. Necklaces assist in tracing migration processes - a neck-rings of Latgallian origin found in grave No 28 of the Ciemalde burial ground proves the relations between the Semigallians and Latgallians. Spiral neck-rings and other jewellery of the Semigallian origin found in Jakštaičiai-Meškiai, Kuršėnai, Paprūdžiai burial grounds show that at the end of the 13th century the migration routes lead to Lithuania. In the 12-13th centuries, the new fashion of wearing necklaces made of brass spirals, glass beads and cowry shells with a hole was spreading. This custom came from the neighbouring tribes of the Lyvonians, Latgallians and Curonians. Few neck-rings were found in the explored old graves of the 14th century; they are similar, however, quite a lot of splendid necklaces made of brass spirals, glass beads and cowry shells were discovered. The custom might have come to Samogitia thanks to the Semigallian migrants.